2017
DOI: 10.1101/234930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specificity of RNAi, LNA and CRISPRi as loss-of-function methods in transcriptional analysis

Abstract: Loss-of-function (LOF) methods, such as RNA interference (RNAi), antisense oligonucleotides or CRISPR-based genome editing, provide unparalleled power for studying the biological function of genes of interest. When coupled with transcriptomic analyses, LOF methods allow researchers to dissect networks of transcriptional regulation. However, a major concern is nonspecific targeting, which involves depletion of transcripts other than those intended. The off-target effects of each of these common LOF methods have… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 83 publications
6
61
0
Order By: Relevance
“…To confirm our findings, we conducted a validation screen targeting the top 25 25 lncRNA candidates identified in the initial screens for mitotic progression and cytokinesis (Supplementary Table 3). Depletion of each lncRNA was performed in two biological (and in total eight technical) replicates.…”
Section: High-content Phenotypic Screen Identified New Lncrnas Involvmentioning
confidence: 69%
See 3 more Smart Citations
“…To confirm our findings, we conducted a validation screen targeting the top 25 25 lncRNA candidates identified in the initial screens for mitotic progression and cytokinesis (Supplementary Table 3). Depletion of each lncRNA was performed in two biological (and in total eight technical) replicates.…”
Section: High-content Phenotypic Screen Identified New Lncrnas Involvmentioning
confidence: 69%
“…2a). Although loc100289019-depleted cells 5 also displayed an elevated mitotic index, levels of the lncRNA did not change upon RNAi 25 . For the cytokinesis category, we observed an increase in the number of cells with cytokinetic bridges after linc00840 depletion and a decrease after loc729970 depletion, but neither led to multinucleation ( Supplementary Fig.…”
Section: High-content Phenotypic Screen Identified New Lncrnas Involvmentioning
confidence: 89%
See 2 more Smart Citations
“…Although other technologies, such as RNAi have been utilized to target Na V 1.7, a recent study has shown that the off-target effects of RNAi, as compared to CRISPRi, are far stronger and more pervasive than generally appreciated 76,77 . In addition, as an exogenous system, CRISPR and ZFPs (unlike RNAi) do not compete with endogenous machinery such as microRNA or RISC complex function.…”
Section: Development Of Targeted Constructsmentioning
confidence: 99%